A Biomarker to Differentiate between Primary and Cocaine-Induced Major Depression in Cocaine Use Disorder: The Role of Platelet IRAS/Nischarin (I1-Imidazoline Receptor) - Keller, Benjamin; Mestre-Pinto, Joan-Ignasi; Álvaro-Bartolomé, María; Martinez-Sanvisens, Diana; Farre, Magí; García-Fuster, M. Julia; García-Sevilla, Jesús A.; Torrens, Marta; , The NEURODEP Group; Fonseca, F.; Mateus, J.; Papaseit, E.; et al. (Frontiers in Psychiatry, 2017)
The association of cocaine use disorder (CUD) and comorbid major depressive disorder (MDD; CUD/MDD); is characterized by high prevalence rates and poor treatment outcomes, CUD/MDD may be Primary (Primary-MDD o Cocaine-Induced (CUD-Induced MDD). Specific biomarkers are needed to improve diagnoses and therapeutic approaches in this dual pathology. Platelet biomarkers (5-HT2A receptor and IRAS/nischarin) were assessed by Western blot in subjects with CUD and primary MDD (n=16) or CUD-induced MDD (n=9; antidepressant-free, AD−; antidepressant-treated, AD+) and controls (n=10) at basal level and/or after acute tryptophan depletion (ATD). Basal platelet 5-HT2A receptor (monomer) was reduced in comorbid CUD/MDD subjects (all patients: 43%), compared with healthy controls, and this downregulation was independent of AD medication (decreases in AD−: 47%, and in AD+: 40%). No basal differences were found for IRAS/nischarin contents in AD+ and AD- comorbid CUD/MDD subjects. The comparison of IRAS/nischarin in the different subject groups during/after ATD showed opposite modulations in response to low plasma tryptophan levels with significant differences discriminating between the subgroups of CUD with primary MDD and CUD-induced MDD. These sspecific alterations suggested that platelet IRAS/nischarin might be useful as a biomarker to discriminate between primary and CUD-induced MDD in this dual pathology.